EDUCATION DEVELOPMENT PROBLEMS IN THE POSTSOVIET SPACE - Chagelishvili-Agladze, Lali (European Scientific Journal, ESJ, 2014)
The current global crisis can only be achieved through a more educated society. The EC’s innovation strategy is the expansion of the capacity of human resources in innovative activity; and the creation of knowledge and its practical application has an important role in knowledge management. The implementation of this strategy in the former-Soviet space is complex and has significant deficiencies. Production and dissemination of knowledge is characteristic of the former-Soviet countries, and is less focused on its practical use for a variety of reasons, among which the most important problems of mentality and language barriers still remain. The elimination of the abovementioned is available by means of creation of the right educational policy and knowledge management system. The most successful companies “understand” that the rejection of knowledge management would be an expensive cost for them. The paper analyzes the development of modern state education and shows the connection between education and development of knowledge management. The author also investigated basic education development problems and cause-effective relationship based on knowledge management and conceptual model of knowledge management is presented. In the final part of the paper the author gives education-related recommendations for problem solution in the former-Soviet space.